The Role of Nonformal Education in Developing the Mental and Spiritual Wellbeing of Participants in the al Amanah Study Group in Palangka Raya - Saifullah Darlan (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
Learning can be done anytime and anywhere, learning does not need to have an age limit. As has been done by the participants of the Al Amanah Palangka Raya study group, which consists of adults and the elderly, aged between 20 to 80 years. Their education and occupation levels vary, ranging from civil servants, retirees, drivers, and laborers. It is intended that this study group has the knowledge, mental spirituality, and strong character so that their lives are calm and they can move well. This research method uses a participatory qualitative approach, with observation techniques, in-depth interviews, and documentation. Data analysis starts from data collection, data condensation, data display, and conclusion and verification. The results showed that, First, the implementation of learning applies adult learning patterns with a family atmosphere, sharing knowledge and respecting each other's opinions. Second, the level of participation of study group participants in following learning is very good. Third, after participating in the learning there are changes in the attitudes and behavior of group members in interacting in the community.